Optimizing the team for required power during track-cycling team pursuit - Heimans, L.; Dijkshoorn, W. R.; Hoozemans, M. J. .; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: Since the aim of the men`s team pursuit in time-trial track cycling is to accomplish a distance of 4000 m as fast as possible, optimizing aerodynamic drag can contribute to achieving this goal. The aim of this study was to determine the drafting effect in second, third, and fourth position during the team pursuit in track cycling as a function of the team members` individual frontal areas in order to minimize the required power. Method: Eight experienced track cyclists of the Dutch national selection performed 39 trials of 3 km in different teams of 4 cyclists at a constant velocity of 15.75 m/s. Frontal projected areas were determined, and together with field-derived drag coefficients for all 4 positions, the relationships between frontal areas of team members and drag fractions were estimated using generalized estimating equations. Results: The frontal area of both the cyclist directly in front of the drafter and the drafter himself turned out to be significant determinants of the drag fraction at the drafter`s position (P?.05) for all 3 drafting positions. Predicted required power for individuals in drafting positions differed up to 35 W depending on team composition. For a team, a maximal difference in team efficiency (1.2%) exists by selecting cyclists in a specific sequence. Conclusion: Estimating required power for a specific team composition gives insight into differences in team efficiency for the team pursuit. Furthermore, required power for individual team members ranges substantially depending on team composition.